Intraperitoneal alpha therapy with 224Ra-labeled microparticles combined with chemotherapy in an ovarian cancer mouse model - Wouters, Roxanne; Westrøm, Sara; Berckmans, Yani; Riva, Matteo; Ceusters, Jolien; Bønsdorff, Tina B.; Vergote, Ignace; Coosemans, An (Frontiers in Medicine, 2022)
A novel alpha-therapy consisting of 224Ra-labeled calcium carbonate microparticles (224Ra-CaCO3-MP) has been designed to treat micrometastatic peritoneal disease via intraperitoneal (IP) administration. This preclinical study aimed to evaluate its efficacy and tolerability when given as a single treatment or in combination with standard of care chemotherapy regimens, in a syngeneic model of ovarian cancer in immune competent mice. Female C57BL/6 mice bearing ID8-fLuc ovarian cancer were treated with 224Ra-CaCO3-MP 1 day after IP tumor cell inoculation. The activity dosages of 224Ra ranged from 14 to 39 kBq/mouse. Additionally, 224Ra-CaCO3-MP treatment was followed by either carboplatin (80 mg/kg)-pegylated liposomal doxorubicin (PLD, 1.6 mg/kg) or carboplatin (60 mg/kg)-paclitaxel (10 mg/kg) on day 14 post tumor cell inoculation. All treatments were administered via IP injections. Readouts included survival, clinical signs, and body weight development over time. There was a slight therapeutic benefit after single treatment with 224Ra-CaCO3-MP compared to the vehicle control, with median survival ratios (MSRs) ranging between 1.1 and 1.3. The sequential administration of 224Ra-CaCO3-MP with either carboplatin-paclitaxel or carboplatin-PLD indicated a synergistic effect on overall survival at certain 224Ra activities. Moreover, the combinations tested appeared well tolerated in terms of weight assessment in the first 4 weeks after treatment. Overall, this research supports the further evaluation of 224Ra-CaCO3-MP in patients with ovarian cancer. However, the most optimal chemotherapy regimen to combine with 224Ra-CaCO3-MP should be identified to fully exploit its therapeutic potential.